Da necessidade da criação de um Código de Processo Constitucional brasileiro - Luiz Fernando Vescovi; Carolina de Cássia Cavalheri (Revista de Derecho)
This research aims to study, in an objective and systematic, factual feasibility of implementing a codified system of standard regards the constitutional processualistic, behold, he pacified the understanding of the autonomy of the legal branch of the Constitutional Procedural Law, from which it extracts laws sparse of writs that compose it, as well as the types of judicial concentrated. The scope of the online investigative proposal is to create a code structure that houses all procedural constitutional manner outlined for the purpose of facilitating the application of rules which has the prerogative to safeguard and / or protect fundamental rights and guarantees (supraindividuals) carved in the Magna Card of 1988, in view of the legal branch alluded still lacks about coding within the national legal system.